2015
DOI: 10.3109/00498254.2015.1081993
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction profile of the HIV integrase inhibitor cabotegravir: assessment fromin vitrostudies and a clinical investigation with midazolam

Abstract: 1. Cabotegravir (CAB; GSK1265744) is a potent HIV integrase inhibitor in clinical development as an oral lead-in tablet and long-acting injectable for the treatment and prevention of HIV infection. 2. This work investigated if CAB was a substrate for efflux transporters, the potential for CAB to interact with drug-metabolizing enzymes and transporters to cause clinical drug interactions, and the effect of CAB on the pharmacokinetics of midazolam, a CYP3A4 probe substrate, in humans. 3. CAB is a substrate for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…The GLS mean ratios and 90% CIs for the differences in steady‐state AUC 0–τ , C max , and C τ between test (LNG/EO + CAB) and reference (LNG/EO alone) treatments were each within the limits of 0.80–1.25, confirming a lack of pharmacokinetically significant interaction between CAB and LNG or EO. These findings are consistent with in vitro and clinical drug interaction studies, which suggested that CAB has minimal interaction liability 7, 12, 13. In addition, steady‐state CAB plasma PK parameters observed in this study were comparable to historical values, suggesting that LNG/EO had no impact on CAB exposure, as expected 12, 13.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The GLS mean ratios and 90% CIs for the differences in steady‐state AUC 0–τ , C max , and C τ between test (LNG/EO + CAB) and reference (LNG/EO alone) treatments were each within the limits of 0.80–1.25, confirming a lack of pharmacokinetically significant interaction between CAB and LNG or EO. These findings are consistent with in vitro and clinical drug interaction studies, which suggested that CAB has minimal interaction liability 7, 12, 13. In addition, steady‐state CAB plasma PK parameters observed in this study were comparable to historical values, suggesting that LNG/EO had no impact on CAB exposure, as expected 12, 13.…”
Section: Discussionsupporting
confidence: 90%
“…Cabotegravir is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT) 1A1 with a minor contribution by UGT 1A9 6. At clinically relevant concentrations, CAB does not inhibit or induce the major cytochrome P450 (CYP) or UGT enzymes in vitro and had no significant effect on the pharmacokinetics (PK) of midazolam, a sensitive CYP3A4 probe substrate 7.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of cabotegravir, these drugs appear to penetrate well to the female genital tract, although exposures are consistently lower than in colorectal tissue, consistent with higher P‐gp expression observed in vaginal tissue over colorectal tissue at mRNA level . In addition to P‐gp, cabotegravir has also been identified as a BCRP substrate; however, due to its high membrane permeability, the effect of transporters on cabotegravir transport may be clinically insignificant . Because target concentrations required for protection in the female genital tract have not been defined for the majority of these drugs, more research is needed to determine whether modulation of drug transporters could influence local tissue concentrations to a degree that plays a significant role in drug efficacy.…”
Section: Role Of Drug‐metabolizing Enzymes and Transporters In Femalementioning
confidence: 98%
“…Cabotegravir is highly bound to serum albumin and has an in vitro protein‐adjusted 90% inhibitory concentration of 166 ng/mL . It is a class 2 compound (Biopharmaceutics Drug Disposition Classification System) exhibiting high passive permeability and low solubility . Cabotegravir is primarily metabolized by uridine diphosphate glucuronosyltransferase (UGT)1A1 with a minor contribution by UGT1A9 to form glucuronic acid conjugates .…”
mentioning
confidence: 99%
“…The primary metabolite, M1, and unchanged cabotegravir are both excreted in bile. Due high intrinsic membrane permeability, the impact of efflux transporters on intestinal absorption of cabotegravir is minimal …”
mentioning
confidence: 99%